(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
Ironically, since European colonisation, there has been a deafening silence of Indigenous representation in all forms and at all societal levels. As Stanner asserts, Indigenous people have been written out of history (1967, p. 22), but the disappearance of our First Nations people is not limited to just the encyclopaedias. Australians have long been viewing media and cinema through a white lens, largely representing an Anglo society, and by its binary, neglecting the Indigenous society that – while subjugated to a near nothingness – remains poignant to this nation’s existence. Indigenous filmmaker Warwick Thornton challenges this white lens in Samson & Delilah (2009), in what has been hailed as Australia’s ‘most important film’ (Redwood 2009, p. 27). Thornton’s film encapsulates the post-colonial state of Indigenous society through a perspective that is rarely shown, but is necessary for the nation and, more generally, the world, to understand the ways in which the First Nations people are subordinated on their own land.